APEC, and how geopolitical tensions could affect the progress of the forum - Aquino Rodríguez, Carlos (2023)
The US trade and technology war with China, and the Russian invasion of Ukraine, are increasing geopolitical tensions that could affect the APEC forum, where those three economies are among the most important members. China and the US seem set to develop parallel supply chains, while the US strengthens its economic and political alliances in Asia. This would impact APEC’s goal of achieving a Free Trade Area in the Asia Pacific, the FTAAP. The other member economies must learn to navigate these tensions between the rivalry of the great powers, which is a hallmark of international economic relations in the future.